2020
DOI: 10.21467/ias.9.1.188-200
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability and Heterosis in Diallel Analysis of Maize (Zea mays L.) Lines

Abstract: A sound breeding program for maize improvement is very important to meet the demands of the growing population. Therefore, combining ability and heterosis were studied in a 4 x 4 full diallel cross in maize for growth attributes, yield and its contributing traits. Randomized Complete Block Design (RCBD) with four replicates was used to study the general combining ability of parents, specific combining ability of F1s (including reciprocals) and heterosis of the F1s over commercial check variety on selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 50 publications
(52 reference statements)
11
3
1
Order By: Relevance
“…The results showed that the general combining ability (GCA) and specific combining ability (SCA) variances were significant or highly significant for all the studied traits, indicating that both additive and non-additive gene action were important in the inheritance of these traits. The present results were inconsistence with those obtained by Rezaei and Roohi (2004) for EH, Srdić et al (2007) for GY, Aly and Mousa (2011) for DTS, PHT, EHT, EP % and GY, Bisen et al (2020) for DTS and PHT and Onejeme et al (2020) for DTS, PHT, EHT and GY traits. The ratio of GCA/SCA was more than unity for all the studied traits, revealing the importance of additive gene action in the genetic control of these traits.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The results showed that the general combining ability (GCA) and specific combining ability (SCA) variances were significant or highly significant for all the studied traits, indicating that both additive and non-additive gene action were important in the inheritance of these traits. The present results were inconsistence with those obtained by Rezaei and Roohi (2004) for EH, Srdić et al (2007) for GY, Aly and Mousa (2011) for DTS, PHT, EHT, EP % and GY, Bisen et al (2020) for DTS and PHT and Onejeme et al (2020) for DTS, PHT, EHT and GY traits. The ratio of GCA/SCA was more than unity for all the studied traits, revealing the importance of additive gene action in the genetic control of these traits.…”
Section: Resultscontrasting
confidence: 99%
“…The ratio of GCA/SCA was more than unity for all the studied traits, revealing the importance of additive gene action in the genetic control of these traits. Similar results were obtained by Dawood et al (1994) and Amer (2002) for DTS, PHT and EHT, Bello and Olaoye (2009) for DTS, PHT and GY, Aly and Mousa (2011) for DTS, PHT, ED and GY, Haydar (2020) for GY, El-Hosary (2020) for DTS and Onejeme et al (2020) for DTS, PHT traits. The mean squares due to GCA x Loc and SCA x Loc were highly significant for all the studied traits, meaning that both additive and non-additive gene effects were affected by environmental.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Most of the authors reported combining ability and heterosis studies in normal corn (Amegbor et al, 2020;Bisen et al, 2020;Elmyhun et al, 2020;Gramaje et al, 2020;Kamara et al, 2020;Keimeso et al, 2020;Khamphasan et al, 2020;Onejeme et al, 2020;Patil et al, 2020;Scaria., 2020;Upreti et al, 2020;Yu et al, 2020;Abdulazeez et al, 2021;Maphumulo et al, 2021;Nyombayire et al, 2021;Riacheet al, 2021) and very few authors ( Dermail et al, 2020;Ravikesavan et al, 2020;Vanipraveena et al, 2021) pertaining to sweet corn. Keeping up with the demand of sweet corn in the market, development of sweet corn hybrids is need of the hour.…”
Section: Identification Of Promising Parental Lines and Hybridsmentioning
confidence: 99%